Proceedings of the Thirtieth International Joint Conference on Artificial Intelligence 2021
DOI: 10.24963/ijcai.2021/65
|View full text |Cite
|
Sign up to set email alerts
|

Budget-feasible Maximum Nash Social Welfare is Almost Envy-free

Abstract: The Nash social welfare (NSW) is a well-known social welfare measurement that balances individual utilities and the overall efficiency. In the context of fair allocation of indivisible goods, it has been shown by Caragiannis et al. (EC 2016 and TEAC 2019) that an allocation maximizing the NSW is envy-free up to one good (EF1). In this paper, we are interested in the fairness of the NSW in a budget-feasible allocation problem, in which each item has a cost that will be incurred to the agent it is allocated to, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 13 publications
2
21
0
Order By: Relevance
“…We also investigate the extent to which an NSW maximizing allocation approximates EF1 in the large budget setting. It has been shown that (for nonidentical valuation functions) such an allocation is 1/2-approximate EF1 [25]. We prove that when agents have identical valuations, this approximation ratio improves and approaches 1, which coincides with the result of Caragiannis et al [5] for the unconstrained setting.…”
Section: Main Results and Techniquessupporting
confidence: 81%
See 4 more Smart Citations
“…We also investigate the extent to which an NSW maximizing allocation approximates EF1 in the large budget setting. It has been shown that (for nonidentical valuation functions) such an allocation is 1/2-approximate EF1 [25]. We prove that when agents have identical valuations, this approximation ratio improves and approaches 1, which coincides with the result of Caragiannis et al [5] for the unconstrained setting.…”
Section: Main Results and Techniquessupporting
confidence: 81%
“…Finally, we consider the large budget setting, in which the agents' budgets are much larger than the sizes of items [11,8,22,18,25]. We show that under this setting, our polynomial-time algorithm computes an allocation whose approximation ratio of EF1 is close to 1.…”
Section: Main Results and Techniquesmentioning
confidence: 99%
See 3 more Smart Citations